1994
DOI: 10.1021/bi00188a028
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Structure and Membrane Localization of Synthetic Segments and a Truncated Form of the IsK (minK) Protein

Abstract: IsK, also referred to as minK, is a membrane protein consisting of 130 amino acids and localized mainly in epithelial cells but also in human T lymphocytes. Depending on the cRNA concentration that was injected into Xenopus oocytes, IsK and its truncated forms can induce either a K+ current alone or both K+ and Cl- currents [Attali et al. (1993) Nature 365, 850-852]. To obtain information on the secondary structure and the topology of IsK in a membrane-bound state, the synthesis, fluorescent-labeling, and stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 45 publications
1
20
1
Order By: Relevance
“…No currents could be evoked, when internally applied C-27 was tested upon hyperpolarization or when it was perfused in the external bath solution (n ϭ 4, 3 batches). A 34-mer hydrophilic peptide (N-34), spanning an amino-terminal region of the rat IsK sequence (position 10 -43) (22), did not evoke any current when injected into the oocyte (at 200 M; n ϭ 5, 3 batches). Other non IsK peptides such as P1, P2, and P3 ( Fig.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…No currents could be evoked, when internally applied C-27 was tested upon hyperpolarization or when it was perfused in the external bath solution (n ϭ 4, 3 batches). A 34-mer hydrophilic peptide (N-34), spanning an amino-terminal region of the rat IsK sequence (position 10 -43) (22), did not evoke any current when injected into the oocyte (at 200 M; n ϭ 5, 3 batches). Other non IsK peptides such as P1, P2, and P3 ( Fig.…”
Section: Resultsmentioning
confidence: 98%
“…A 27-mer hydrophilic peptide (C-27), spanning a carboxyl-terminal region of the rat IsK sequence (positions 68 -94) (22) and located immediately downstream from the transmembrane segment, was synthesized and microinjected into Xenopus oocytes (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our investigation showed that while the NT domain is predominantly non-ordered in aqueous solution at 20 o C, increased temperature or interaction with lipid increases the tendency to form helix, perhaps by adoption of some 3 10 helix, indicating conformational flexibility. This suggests some structural similarity with MinK NT domain, which adopts a predominantly helical conformation in methanol as determined by CD spectroscopy [35]. Furthermore, results from fluorescence emission spectroscopy suggest that MinK NT partially inserts into phosphatidylcholine vesicles, although it was not reported whether this is accompanied by any structural switch [36].…”
Section: Mirp1 N-terminal (Nt) Extracellular Domainmentioning
confidence: 99%
“…It has been suggested that several I~K subunits may aggregate together to directly form a pore-containing structure [7]. An alternative proposal is that IsK itself is not a channel forming protein but acts as a modulator of endogenous oocyte channels [8,9] In this study we have investigated the functional role of a region of the putative transmembrane domain of IsK by constructing several site-directed mutants, in which individual amino acid residues have been substituted by cysteine, followed by expression in Xenopus oocytes. …”
mentioning
confidence: 99%